4S‐AF scheme and ABC pathway guided management improves outcomes in atrial fibrillation patients. (1st February 2022) - Guo, Yutao; Imberti, Jacopo F.; Kotalczyk, Agnieszka; Wang, Yutang; Lip, Gregory Y. H.; ,
Abstract: Background: The 4S‐AF scheme and the ABC pathway for integrated care have been proposed to better characterize and treat patients with atrial fibrillation (AF). We aimed to evaluate the assessment of the 4S‐AF scheme and ABC pathway in Chinese AF patients. Methods: The ChiOTEAF is a prospective, observational, multicentre registry. Consecutive AF patients from 44 centres across 20 Chinese provinces with available 1‐year follow‐up data were included. Results: A total of 6419 patients were included, median age 76 years (interquartile range 67–83; 39.1% female). Of these, 3503 (59.8%) patients were not characterized using the 4S‐AF scheme and not management according to the ABC pathway (group 1); 1795 (28.0%) were characterized according to the 4S‐AF scheme but ABC pathway non‐adherent or vice versa (group 2); and 1121 (17.4%) characterized according to the 4S‐AF scheme and were ABC pathway adherent (group 3). As compared with group 1, group 2 and group 3 were independently associated with lower odds of the composite endpoint of all‐cause death/any thromboembolic event, with the greatest benefit observed in group 3 (OR: 0.19; 95% CI 0.12–0.31) [for group 2: OR: 0.28; 95% CI 0.20–0.37]. Similar results were observed for all‐cause death (group 2: OR: 0.18; 95% CI 0.12–0.27; group 3: OR: 0.14; 95% CI 0.07–0.25). Conclusions: In a contemporary real‐word cohort of Chinese AF patients, it is feasible to characterize and manage AF patients using the novel 4S‐AF scheme and ABC pathway for integrated care. The use of both these tools is associated with improved clinical outcomes.